A Technical Report on the Development of an Analytical Calculator for the Design of Hydraulic Sections for Open Channel Flows (2022)
Hydraulic structures are designed for conveyance, structural integrity and sustainability. Flood prevention and control is more than ever creating a significant gap for the research society. Particularly for the southern and deltaic regions of the globe. The ease of design embodies the beauty of design. With the ever-rising climatic effects on the earth primarily due to human activities, and prevalent rise in global sea and river levels, the design of channels to manage water bodies in cities and towns is of primary importance. This paper uses basic hydraulic principles to develop analytical equations which were programmed in Microsoft Excel to design for all sectional properties of op ’n channels as well as plot the cross section of the channel using four key variables of peak flow, channel bed sk ;e, c^ainel side slope, and roughness coefficient. The developed model is an enhanced calculator in the hydraulic engineering society due to its ability to function satisfactorily without prior knowledge of base with or flow depth